2006
DOI: 10.1002/ptr.1897
|View full text |Cite
|
Sign up to set email alerts
|

Studies on hepatoprotective, antispasmodic and calcium antagonist activities of the aqueous‐methanol extract of Achillea millefolium

Abstract: The crude extract of Achillea millefolium (Am.Cr) was studied for its possible hepatoprotective effect against d-galactosamine (d-GalN) and lipopolysaccharide (LPS) induced hepatitis in mice and antispasmodic effect in isolated gut preparations to rationalize some of the folklore uses. Co-administration of d-GalN (700 mg/kg) and LPS (25 microg/kg) produced 100% mortality in mice. Pre-treatment of animals with Am.Cr (300 mg/kg) reduced the mortality to 40%. Co-administration of d-GalN (700 mg/kg) and LPS (1 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 12 publications
2
47
0
4
Order By: Relevance
“…Moringa oleifera, known to be rich in multiple medicinally active chemicals, may be a good candidate to see if it contains effect enhancing and/or side-effects neutralizing combinations. Medicinal plants are relatively rich in their contents of calcium channel blockers (CCBs) which are known to possess a wide variety of pharmacological activities such as antihypertensive, hepatoprotective, antiulcer, antiasthmatic, antispasmodic and antidiarroeal (Stephens and Rahwan, 1992;Gilani et al, 1994b;2005b;Yaeesh et al, 2006; and it remains to be seen whether such activities reported to be present in Moringa oleifera have a direct link with the presence of CCBs.…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moringa oleifera, known to be rich in multiple medicinally active chemicals, may be a good candidate to see if it contains effect enhancing and/or side-effects neutralizing combinations. Medicinal plants are relatively rich in their contents of calcium channel blockers (CCBs) which are known to possess a wide variety of pharmacological activities such as antihypertensive, hepatoprotective, antiulcer, antiasthmatic, antispasmodic and antidiarroeal (Stephens and Rahwan, 1992;Gilani et al, 1994b;2005b;Yaeesh et al, 2006; and it remains to be seen whether such activities reported to be present in Moringa oleifera have a direct link with the presence of CCBs.…”
Section: Future Prospectsmentioning
confidence: 99%
“…β-Carotene of M. oleifera leaves exerts a more significant protective activity than silymarin against antitubercular induced toxicity. It would be interesting to see if it also possesses hepatoprotective effect against other commonly used hepatotoxic agents such as CCl 4 and galactosamine, which are considered more suitable models and close to human viral hepatitis (Gilani and Janbaz, 1995;Yaeesh et al, 2006).…”
Section: Future Prospectsmentioning
confidence: 99%
“…In Pakistan (Said, 1982;Yaeesh et al, 2006), A. millefolium L. has been recognized as a diaphoretic and stimulant medicinal plant which can treat various liver diseases (see Table 2). …”
Section: Historical Traditional and Ethnomedicinal Uses Of The Achilmentioning
confidence: 99%
“…A diaphoretic, stimulant, antipyretic, analgesic, anti-inflammatory, antispasmodic, carminative, antihelmentic, hepatoprotective, antispasmodic remedy; in the treatment of various liver diseases Pakistan (Said, 1982;Yaeesh et al, 2006) A. millefolium L. Effective anti-inflammatory, analgesic, antispasmodic, and antiseptic properties Brazil (Cavalcanti et al, 2006) A. millefolium L.…”
Section: Herbal Tea; In the Lotions And Ointments For External Uses Imentioning
confidence: 99%
“…Antihepatoprotective, antispasmodic and calcium antagonistic activity was reported in the aqueous methanolic extract of Achillea millefolium (Yaeesh et al, 2006). The plant has shown antiulcer efficacy after chronic treatment in winter rats (Cavalcanti et al, 2006).…”
Section: Phytochemical Constituentsmentioning
confidence: 99%